Kematangan Emosi sebagai Faktor Penentu Perilaku Mengemudi Agresif di Kalangan Pengemudi Ojek Online - Ariq Rahmat Rizki; Nurul Huda; Dina Kusuma Astuti (Lembaga Pengembangan Kinerja Dosen, 2025)
The increasing number of online motorcycle taxi drivers joining app-based transportation services has created a new phenomenon on the roads. One of the consequences is the potential for increased traffic congestion and the emergence of less conducive road conditions. This situation can trigger aggressive driving behavior among online motorcycle taxi drivers, which may ultimately lead to accidents. This study aims to empirically examine the relationship between emotional maturity and aggressive driving behavior among online motorcycle taxi drivers. The approach used in this research is a quantitative method. The sampling technique applied is purposive sampling, and data analysis was conducted using Pearson Product Moment correlation. The instrument used to measure aggressive driving was the Aggressive Driving Behavior Scale (ADBS), developed by Houston, Harris, and Norman, which includes conflict behavior and speeding. Meanwhile, the emotional maturity scale was constructed based on aspects proposed by Walgito, such as acceptance of oneself and others, emotional control, non-impulsiveness, responsibility, and objective thinking. The hypothesis testing results showed a significance value of 0.000 (p<0.0001) with a correlation coefficient (r) of -0.544. These findings indicate a highly significant negative relationship between emotional maturity and aggressive driving behavior among online motorcycle taxi drivers.